FUNGSI BADAN PERMUSYAWARATAN DESA DALAM MENAMPUNG DAN MENYALURKAN ASPIRASI MASYARAKAT DESA SELALEJO, KECAMATAN MAUPONGGO, KABUPATEN NAGEKEO - bule, kornelis (Jurnal Ilmiah Dinamika Sosial, 2018)
ABSTRACTVillage Consultative Body function in accommodating and aspirations of rural communities Selalejo, District Mauponggo, Nagekeo District. Issues examined in this research is how the function of the Village Consultative Body Selalejo in accommodating the aspirations of rural communities and districts Selalejo Mauponggo, Ngada. The aim of this study was to determine the function of the village consultative body (BPD) Selalejo, District Mauponggo, Nagekeo District in accommodating and aspirations of society. This research was conducted in the village of Selalejo, District Mauponggo, Nagekeo District. Data collection technique used observation, documentation and interview. The data were then analyzed using descriptive qualitative data analysis techniques, where researchers convey information obtained by processed, interpreted and examined in detail from observations and interviews. The results showed that the Village Consultative Body Function in accommodating and aspirations of rural communities Selalejo, District Mauponggo, Nagekeo District, was in accordance with the mandate of the law no. 6 of 2014 villages of the local government. These results were obtained from the information that is obtained when the researchers conducted observations in the village Selalejo and also some interviews done to society Selalejo, Chairman of the BPD, BPD members selalejo.Keywords: Village Consultative Body Function